PERSEPSI GURU TERHADAP SUPERVISI OLEH KEPALA SEKOLAH DAN KETERKAITANNYA DENGAN KINERJA GURU SMPN 99 JAKARTA - Irmawati Irmawati (Jurnal Manajemen Pendidikan, 2010)
The objective of this study is to find out the relationship between teacher perception to supervision by headmaster and performance of the teachers in SMP 99 Jakarta. This research is done at SMPN 99 Jakarta for three months since June until August 2009. Method of the research are quantitative method. Target population are 57 and samples are 30 respondents by using simple random sampling. Questionnaire is used to collecting data. This research bring into the conclusion that are relationship between teacher perception to supervision by headmaster and performance of the teachers, in other words the performance of those teachers might be influenced by their supervision.